Phenotypic and genotypic characterization of carbapenem-resistant Acinetobacter baumannii isolates from Egypt - Abouelfetouh, Alaa (Antimicrob Resist Infect Control, 2019)
BACKGROUND: Antibiotic use is largely under-regulated in Egypt leading to the emergence of resistant isolates. Carbapenems are last resort agents to treat Acinetobacter baumannii infections resistant to other classes of antibiotics. However, carbapenem-resistant isolates are emerging at an alarming rate. This study aimed at phenotypically and molecularly characterizing seventy four carbapenem-unsusceptible A. baumannii isolates from Egypt to detect the different enzymes responsible for carbapenem resistance. METHODS: Carbapenemase production was assessed by a number of phenotypic methods: modified Hodge test (MHT), carbapenem inactivation method (CIM), combined disc test (CDT), CarbAcineto NP test and boronic acid disc test. Polymerase chain reaction (PCR) was used to screen the isolates for the presence of some genes responsible for resistance to carbapenems, as well as some insertion sequences. RESULTS: PCR amplification of class D carbapenemases revealed the prevalence of bla(OXA-51) and bla(OXA-23) in 100% of the isolates and of bla(OXA-58) in only one isolate (1.4%). bla(VIM) and bla(NDM-1) belonging to class B metallo-β-lactamases were present in 100 and 12.1% of the isolates, respectively. The prevalence of ISAba1, ISAba2 and ISAba3 was 100, 2.7 and 4.1%, respectively. None of the tested isolates carried bla(OXA-40), bla(IMP), bla(SIM), bla(SPM), bla(GIM) or the class A bla(KPC). Taking PCR as the gold standard method for the detection of different carbapenemases, the sensitivities of the MHT, CIM, CDT, CarbAcineto NP test and boronic acid disc/imipenem or meropenem test for this particular collection of isolates were 78.4, 68.9, 79.7, 95.9, and 56.8% or 70.3%, respectively. CONCLUSIONS: The widespread detection of carbapenem-resistant A. baumannii (CR-AB) has become a real threat to the efficacy of treatment regimens. Among the studied cohort of CR-AB clinical isolates, bla(OXA-51), bla(OXA-23) and bla(VIM) were the most prevalent, followed by bla(NDM-1) and bla(OXA-58). The genotypic detection of carbapenemases among CR-AB clinical isolates using PCR was most conclusive, followed closely by the phenotypic testing using CarbAcineto NP test.